Wear and corrosion behavior of Mg-based alloy reinforced with TIC and ZrC particles - Odabasi, Hulya Kaftelen; Odabasi, Akin (Carl Hanser Verlag, 2020)
In this contribution, particle sizes of TiC (13 and 93 mu m) and volume fractions of ZrC (5 and 10 vol.-%) with respect to reinforcement particles were varied to investigate the effects on the microstructure, hardness, density, wear and corrosion properties of AZ91 Mg matrix alloy. Experimental results revealed that the hardness, density and sliding wear performance of AZ91 alloy were markedly improved by the addition of carbide particles. Predominant wear and corrosion mechanisms were identified considering the size and volume fraction of the carbides. The composite sample comprising fine TiC particles (13 mu m) exhibited the highest wear resistance at the same volume fraction as the coarse particles. Moreover, coarse ZrC particles with a low volume fraction (5 vol.-%) provided an enhanced wear resistance beyond that of the 10 vol.-% ZrC particles. Considering all the investigated composites, the corrosion resistance of the composites deteriorated with the increasing volume fraction and size of the carbide particles. Electrochemical measurements of the 0,5M NaCl solution revealed that increasing carbide particle size and volume fraction leads to lower corrosion resistance due to the formation of more cathodic areas which are preferred sites for the initiation of pitting corrosion.
Keywords: Composites; metalic matrix; corrosion; wear; magnesium